Experimental and numerical studies for flow over a sierpinski tetrahedron for potential windbreak application. Issue 216 (September 2021) - Lim, Y.S.; Wang, P.C.; Yeo, J.J.; Yu, S.C.M.
Abstract: Investigations have been conducted to study the flow characteristics behind the Sierpinsksi Tetrahedron to assess its potential as windbreaks. Sierpinski Tetrahedrons are fractal sets with an equilateral triangle as its based shape. The upper levels consist of subdivided small equilateral triangles until the apex is reached. Flow over the Sierpinski Tetrahedron at Re = 39, 400 and 65, 700 were analyzed in an open circuit wind tunnel and the measured velocities were used to validate the numerical simulation results. The validated numerical simulation results showed good agreement in general with the experimental data. 5 models are subsequently chosen to be investigated further numerically, at different orders of fractal sets, from order 0 to order 4. RANS numerical model was used with wind speeds ranging from Reynolds number 2.79 × 10 5 to 4.48 × 10 6 . The results reveals that higher orders are more effective in reducing wind speed. The percentage in wind speed reduction measured at a distance of 12H (H being the height of the Sierpinski Tetrahedron) away from the Sierpinski Tetrahedron is 32% for orders 2, 3 and 4. Order 4 which has highest porosity has the lowest peak turbulence intensity and highest speed reduction. The present study also shows that staggered formation of laying the Sierpinski Tetrahedrons as windbreaks could help in providing a greater coverage area. Highlights: The findings of this study have shown that the Sierpinski model has good potential to be used as windbreaks. Experimental and numerical studies has been carried to study the characteristics of flow over a sierpinski tetrahedron. Numerical results were validated with wind tunnel experiments. Flow velocities before and aft of the sierpinski setrahedron were measured using Laser Doppler Velocimetry (LDV). Order 3 Sierpinski tetrahedron is recommended to be the highest order that should be selected as a windbreak.